Solve the linear-quadratic system of equations algebraically. Show your step-by-step work.

y=−x^2+2x−3
y=4x−3

1 answer

To solve the linear-quadratic system of equations algebraically, we need to find the values of x and y that satisfy both equations simultaneously.

First, we can set the two equations equal to each other since they both equal y:
−x^2+2x−3 = 4x−3

Next, we can simplify the equation:
−x^2+2x−3 = 4x−3
-x^2 + 2x = 4x

Moving all the terms to one side of the equation:
-x^2 - 4x + 2x = 0

Combining like terms:
-x^2 - 2x = 0

Factoring out an x:
x(-x - 2) = 0

Setting each factor equal to zero:

x = 0 or -x - 2 = 0

If x = 0:
Using one of the original equations, y = 4x - 3:
y = 4(0) - 3
y = -3

If -x - 2 = 0:
-x = 2
x = -2

Using one of the original equations, y = 4x - 3:
y = 4(-2) - 3
y = -11

Therefore, the solutions to the linear-quadratic system of equations are (0, -3) and (-2, -11).
Similar Questions
    1. answers icon 6 answers
  1. Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below.Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x
    1. answers icon 2 answers
    1. answers icon 1 answer
  2. JamalStep 1: Set equation =0 . x2+4x−12=0 Step 2: Write quadratic equation as the product of two factors. (x+6)(x−2)=0 Step
    1. answers icon 2 answers
more similar questions